The Relationship between Learning Motivation of Citizens Learning to the Learning Outcomes of the Package C Program at PKBM Sentosa Hati - Yolanda Rismawati; Fandi Ahmad Zikri; Dea Monica; Dalvino Yuliandoni; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This study aims to find out: (1) learning motivation of citizens learning program equivalents of C package PKBM Sentosa Hati, (2) learning outcomes of residents learning equality program packages C PKBM Sentosa Hati and (3) the relationship of learning motivation with learning outcomes in citizens learning programs equality package C PKBM Sentosa Hati. This study uses a quantitative approach. The type of research is correlational. This research is a study that involved a population of 47 learning citizens. Data were collected by a research instrument in the form of a questionnaire and documentation. The data analysis technique used is the percentage and product-moment correlation. The learning motivation of the citizens to learn the equivalence program of Package C at Sentosa Hati PKBM is 38.4 or in the low category. The average/mean learning outcomes of the C package program at PKBM Sentosa Hati is 71 or in the medium category. There is a positive and significant relationship between learning motivation and the learning outcomes of citizens learning the C package program at PKBM Sentosa Hati. This is indicated by the value of r count greater than r table (from r table (2.25> 2.07) 5% significance level.Keywords: Program, Education, Nonformal, Elderly